Initial results analysis of kidney transplantation of cadaveric donor program in Pará State. - Fonseca , Aluízio Gonçalves da; Mignone , Silvia Cruz; Ponte , José Ricardo Tuma da; Lima, Simone Martins; Cruz , Sidney Antonio; Souza , Fernando Jordão de; Toscano , Paulo Martins; Almeida , Mauro Ferreira de (Brazilian Journal of Transplantation, 2005)
Objective: The renal transplantation program from cadaveric donor in Estado do Pará - Brazil has started in December 2000. This work aims to assess the early outcomes from this program, as well as identify the main risk factors related to the graft loss. Methods: 51 cadaveric donor kidney transplantations were retrospectively analyzed as for the graft survival and patient survival in 1, 3 and 5 years. The graft survival has served as censure while analyzing the importance of several risk factors. For survivals analysis the Kaplan-Meier method was used. The univariate and multivariate Cox proportional hazards regression analysis was used for the risk factors. Results: The graft survival and patient survival in 1, 3 and 5 years were respectively 91%, 81% and 81% and 93%, 89% and 89%. Death with functioning graft occurred in 62.5% of patients. The donors’ risk factors had no inﬂuence on graft loss. Chronic rejection, positive serology to cytomegalovirus and hepatitis B or C, surgical complications and dialysis time were signiﬁcant in the univariate analysis for graft loss, among the recipient’s risk factors. Conclusion: The early outcomes of this program were satisfactory. Death with functioning graft represented important failure cause. Measurement forward to improve the clinical pre-operative evaluation and to act in risk factors must be emphasized, aiming to improve the long-term outcomes of kidney transplantation from cadaveric donor.